PENGARUH POSISI BERSALIN LATERAL TERHADAP RUPTUR PERINEUM PADA KALA II IBU PRIMIPARA - Hestri Norhapifah (Jurnal Medika : Karya Ilmiah Kesehatan, 2018)
Bleeding is the major cause of death in which one of them can be caused by a rupture of the perineum. The use of maternity lateral position on the second stage can minimize the risk of lacerations of the perineum and labor is more convenient. Objective to determine the effect of lateral position in preventing rupture of the perineum in the second stage of primiparous.The method in this study is using Quasi Experiment with post test only approach with non equivalent control group design. The sampling technique used consecutive sampling with a sample 31 for intervention group and 31 for control group. Data was analyzed using bivariate analysis stage using chi-square test, the calculation interval cofidence OR with 95% and regression analysis.Results there was an effect of lateral position in preventing rupture of perineum or reduce the degree of rupture perineum in the second stage of primiparous with multivariate analysis values obtained OR 9,68 (95% CI= 2,08-45,0).Mothers who gave birth with lateral position on the second stage can prevent rupture of perineum or reduce the degree of rupture perineum compared with mothers who gave birth with a half-sitting position.